The use of Make a Match in teaching reading comprehension: Investigating the students’ achievement and attitude. - Wiwik Mardiana (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
Make a Match method employed by Curran (1994) has some advantages in teaching especially reading comprehension in English. Thus, the purposes of this study are examining the effectiveness of make a match in teaching reading comprehension that is measured from the students’ achievement and the students’ attitude which is compared to the achievement. This study used mixed method of convergent parallel design combining quantitative (Quasi experimental) and qualitative. The data was gained from test (pre-test and post-test), interview and observation. The result of this research showed that “Make a Match” method was effective to teach reading comprehension especially in reading report text. Based on the post-test result of the reading comprehension achievement of the students who are taught using “Make a Match” method (experimental group) is significantly higher than those who are taught without using “Make a Match” method (control group). The achievement was affected by the students’ attitude that they were motivated by showing their enthusiasm and participation when “Make a Match” method was applied